Structuring an educational health product about the Kangaroo Method: experience report with the use of the CTM3 Method (Research, Society and Development, 2022)
This study addresses the structuring of an educational product for use in health education on the Kangaroo Method. This is a descriptive study of the experience report type, with a qualitative approach, for the purpose of presenting the construction of an educational video. The structuring was based on the CTM3 Method, composed of elements didactically grouped in 03 stages: Product design (C); Theoretical reference (T); and Methodological framework based on three theories (M3): Transactional Analysis, which works with the mechanisms of the personality framework that shape EGO states (Father, Adult and Child); Multisensoriality, which involves the perception of the five senses (hearing, vision, smell, gustatory and touch/kinesthetic); and Neurolinguistic Programming (NLP), which addresses subliminal aspects of communication with the use of tools, highlighting here the anchor. Educational products are important teaching tools. Educational videos have been used in several pedagogical experiences, demonstrating their relevance to the teaching-learning process. The need for correct structuring is essential for the proper use of an educational resource and in accordance with the learning objectives. In this way, the CTM3 Method directs to the knowledge and how to make the different types of educational products. It is concerned with the impact and scope of educational resources, working on communication, and reinforcing the potential for acquiring knowledge and improving the learning experience. It proved to be effective in the development of communication for professional health education, with a well-planned structure consistent with technical-scientific quality.